Quantification and influencing factors of perioperative hidden blood loss in patients undergoing laparoscopic ovarian cystectomy for benign ovarian tumours - Junhan Zhou; Miaomiao Ye; Wenxiao Jiang; Xueqiong Zhu (Journal of Obstetrics and Gynaecology, 2022)
AbstractThis retrospective, monocentric study quantified hidden blood loss (HBL) and investigated its influencing factors in benign ovarian tumour patients undergoing laparoscopic ovarian cystectomy. Data from 153 patients who underwent laparoscopic ovarian cystectomy were retrospectively reviewed. HBL was calculated using the formula derived from ‘Nadler’ and ‘Cross’. Pearson correlation was carried out to measure the association between HBL and potential risk factors. The average HBL was 280.22 ± 168.42 mL, accounting for 84.13 ± 19.20% of total blood loss (TBL) (347.48 ± 179.05 mL), which was a change of almost fourteen-fold relative to median visible blood loss [20.00 mL (10.00 mL, 57.5 mL)]. Surgical time, number of excisional tumours and preoperative albumin values were risk factors for HBL. HBL represents a large proportion more than 80% of TBL in patients undergoing laparoscopic ovarian cystectomy. Collectively, HBL is helpful for estimating intraoperative blood loss and better guidance of haemostatic agents, which reduces postoperative complications and expedites postoperative recovery. Additionally, the estimation of HBL also contributes to the summary, reflection and improvement of surgical technique.IMPACT STATEMENTWhat is already known on this subject? There has been a growing number of surgical patients with perioperative anaemia, which appears to be inconsistent with measured levels of visible intraoperative blood loss and postoperative drainage. This substantial but easily underestimated blood loss is known as hidden blood loss. To date, no published articles have evaluated HBL and its related risk factors in benign ovarian tumour patients undergoing laparoscopic ovarian cystectomy.What the results of this study add? HBL accounts for a large amount of TBL in laparoscopy for benign ovarian tumours. Surgical time, number of excisional tumours and preoperative albumin values are risk factors for HBL.What the implications are of these findings for clinical practice and/or further research? The management of HBL is important for the administration of perioperative blooding loss. In this context, HBL can be applied to estimate intraoperative blood loss and be better guidance of haemostatic agents to reduce postoperative complications and hasten postoperative rehabilitation. Additionally, the estimation of HBL also contributes to the summary, reflection and improvement of surgical technique.